Предмет: Математика,
автор: littel2005
Упростите выражение
1,2(2х-1)+3,5(х-2)+10,2
Ответы
Автор ответа:
0
1,2(2х-1)+3,5(х-2)+10,2= 2,4x - 1,2 + 3,5x - 7 + 10,2 = 5,9x + 2
Автор ответа:
0
1,2(2х - 1) + 3,5(х - 2) + 10,2 = 2,4х - 1,2 + 3,5х - 7 + 10,2 = 5,9х + 2,0
Автор ответа:
0
1,2(2х - 1) + 3,5(х - 2) + 10,2 = 2,4х - 1,2 + 3,5х - 7 + 10,2 = 5,9х + 2,0
Похожие вопросы
Предмет: Физика,
автор: pogchampst2
Предмет: Математика,
автор: umenyakoronavirus
Предмет: Химия,
автор: gagaga66
Предмет: Биология,
автор: kate067002